DUKUNGAN MANAJEMEN DAN INFRASTRUKTUR TEKNOLOGI SEBAGAI FAKTOR PENENTU PENGGUNAAN SISTEM INFORMASI AKUNTANSI PADA UMKM - Esti Saraswati; Lusi Yuliarti (Politeknik Negeri Ambon, 2025)
Introduction: This research investigates the role of management support and technological infrastructure in influencing the usage of Accounting Information Systems (AIS) among micro, small, and medium enterprises (MSMEs) in South Purwokerto District. Methods: Using a quantitative approach, the study employs multiple linear regression analysis with using SPSS software, based on data collected from 150 MSME respondents. Results: The results reveal that technological infrastructure significantly affects AIS usage positively, while management support does not exert a significant partial influence. These findings suggest that the availability and quality of technological resources such as hardware, software, and internet connectivity play a critical role in supporting digital system implementation. On the other hand, managerial involvement alone may not be sufficient to increase AIS adoption if not supported by technical readiness. This supports the Technology Acceptance Model (TAM), particularly the perceived ease of use, which is shaped by infrastructure adequacy. The implication of this study emphasizes the need for MSME stakeholders to improve their digital literacy and infrastructure to optimize AIS utilization. Moreover, adaptive leadership and policy strategies are necessary to support successful digital transformation within the MSME sector. Keywords: accounting information